Karakteristik yoghurt rumput laut dengan konsentrasi Gracilaria sp. yang berbeda menggunakan kombinasi bakteri Lactobacillus plantarum dan Streptococcus thermophiles: Characteristics of Seaweed Yoghurt with Different Concentration of Gracilaria sp. Using A Combination of Lactobacillus plantarum and Streptococcus thermophilus - Eko Nurcahya Dewi; Alifa Nur Fauziah; Lukita Purnamayati (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2023)
Gracilaria sp. is a widely produced red alga that can be cultivated. Yoghurt is a healthy food fermented by Lactobacillus plantarum and Streptococcus thermophilus, but currently, there are many ways to produce yoghurt with a combination of several ingredients from another animal source. This study aimed to determine the effect of Gracilaria sp. addition to the characteristics of seaweed yoghurt fermented by L. plantarum and S. thermophilus bacteria. The research used a completely randomized design (CRD) with the addition of Gracilaria sp. at different concentrations (30%, 40%, and 50%). The results showed that the addition of different Gracilaria sp. concentrations affect protein content, fat content, total titratable acidity value, pH value, total LAB, and hedonic value. The best concentration in Gracilaria sp. addition was 30%, because it had a total LAB 6.29 Log (cfu/mL) and hedonic test preferred by consumers in the interval 6.50<µ<6.55.